Determinants of foreign exchange risk management in Latin American firms. Issue 4 (26th November 2019) - Giraldo-Prieto, César Augusto; De Fuentes, Cristina; Sogorb-Mira, Francisco
Abstract : Purpose: The purpose of this paper is to identify whether Latin American (LA) firms are adopting any hedging strategy when designing foreign exchange risk (FXR) measures. To that end, the authors explore the impact of several drivers of FXR management. Design/methodology/approach: The sample consists of 342 non-financial listed firms established in a group of representative countries of the LA region and covers the period from 2008 to 2016. Hypothesis testing is performed through a Logit model that measures the likelihood to adopt hedging practices. In addition, a Tobit test offers further insights into the derivatives users. Findings: The authors corroborate capital structure-related hypotheses such as tax goals, financial distress, liquidity and growth opportunities. In addition, both ownership concentration and income tax payable seem to be negative and significant determinants of FXR coverage. Originality/value: Results reported in this study are relevant for the LA region with high tradition in raw materials and commodities exports. The results show that LA firms still make limited use of derivatives and there is still much room for improvement. Hence, additional efforts to promote FXR hedging should be desirable, to meet authorities' recommendations (OECD et al., 2007). Further research exploring corporate governance relationships and differences between large and small firms might be helpful. Abstract : Propósito: Este estudio tiene como objetivo identificar si las empresas Latinoamericanas (LA) están adoptando alguna estrategia de cobertura frente al riesgo de tipo de cambio (FXR). Para ello exploramos el impacto de varios determinantes de gestión de FXR. Diseño/metodología/enfoque: La muestra está formada por 342 empresas del sector no financiero de un grupo representativo de países latinoamericanos y abarca el período 2008 a 2016. Para testar las hipótesis se aplican modelos Logit que miden la probabilidad de adoptar diferentes prácticas de cobertura. Adicionalmente, los resultados de la aplicación de un modelo Tobit ofrecen información extra sobre los usuarios de derivados. Hallazgos: Corroboramos las hipótesis relacionadas con la estructura de capital, tales como objetivos fiscales, dificultades financieras, liquidez y oportunidades de crecimiento. Además, tanto la concentración de propiedad como los impuestos sobre la renta por pagar parecen ser determinantes negativos y significativos de la cobertura de FXR. Originalidad/valor: Los resultados reportados en este estudio son relevantes para la región Latinoamericana con una gran tradición en exportaciones de materias primas y productos básicos. Nuestros resultados muestran que las empresas Latinoamericanas utilizan de manera limitada los derivados y todavía hay mucho por mejorar. Por lo tanto, es deseable la promoción de esfuerzos adicionales en cuanto a la cobertura de FXR para cumplir con las recomendaciones de las autoridades (OECD, 2007). Entre otras, serían de gran ayuda las investigaciones adicionales que exploren factores adicionales de Gobierno Corporativo (CG) así como profundizar en las diferencias entre empresas grandes y pequeñas.